A Report on Climate Smart Feed and Forages Training Bale Zone, Oromia - Asfaw, Addisu; Mekonnen, Kindu; Gebreyes, Million; Seifu, Haimanot (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Livestock production and productivity are very low in Ethiopia. Poor quality and inadequate quantity of feeds are major constraints in the Ethiopian highlands. The farming system in Bale zone, where AICCRA project has been operating, is dominated by production of wheat as a major food and cash crop. Most grazing lands changed to cultivated lands due to increasing human population. Wheat straw has been the major livestock feed in the area, which is low in palatability and nutritional value. As a result, livestock production and productivity have been declining from time to time. Therefore, the introduction of climate smart feed and forage innovations into the area becomes crucial. It will have an added value to supplement the available feed and forage and, in the long run, transform livestock production and productivity. To overcome the livestock feed and associated problems, the government seeks active engagements from NGOs, government lead projects, national and international research institutions, higher education institutions, and private sectors. To achieve this objective, capacitating experts, development agents and farmers is crucial. In line with this objective, AICCRA and TAAT projects have been jointly working and providing training on climate smart feed and forage innovations, organizing experience sharing visits and practicing a forage seed supply scheme in a revolving seed system approach. More than 400 households (>36% female), 18 DAs and 8 experts engaged in the recently organized theoretical and practical training program. The training was delivered from 10-22 July 2023 at each kebele level in two districts (Sinana and Goba). Representative farmers from eight kebeles managed to attend the training. This report covers the trainings delivered at kebele level, objectives of the training, mode of training delivery and the number of beneficiaries.